Hyperpolarized (3)He magnetic resonance imaging ventilation defects in asthma: relationship to airway mechanics - Leary, Del (Physiol Rep, 2016)
In patients with asthma, magnetic resonance imaging (MRI) provides direct measurements of regional ventilation heterogeneity, the etiology of which is not well‐understood, nor is the relationship of ventilation abnormalities with lung mechanics. In addition, respiratory resistance and reactance are often abnormal in asthmatics and the frequency dependence of respiratory resistance is thought to reflect ventilation heterogeneity. We acquired MRI ventilation defect maps, forced expiratory volume in one‐second (FEV (1)), and airways resistance (Raw) measurements, and used a computational airway model to explore the relationship of ventilation defect percent (VDP) with simulated measurements of respiratory system resistance (R(rs)) and reactance (X(rs)). MRI ventilation defect maps were experimentally acquired in 25 asthmatics before, during, and after methacholine challenge and these were nonrigidly coregistered to the airway tree model. Using the model coregistered to ventilation defect maps, we narrowed proximal (9th) and distal (14th) generation airways that were spatially related to the MRI ventilation defects. The relationships for VDP with Raw measured using plethysmography (r = 0.79), and model predictions of R(rs>14) (r = 0.91, P < 0.0001) and R(rs>9) (r = 0.88, P < 0.0001) were significantly stronger (P = 0.005; P = 0.03, respectively) than with FEV (1) (r = −0.68, P = 0.0001). The slopes for the relationship of VDP with simulated lung mechanics measurements were different (P < 0.0001); among these, the slope for the VDP‐X(rs0.2) relationship was largest, suggesting that VDP was dominated by peripheral airway heterogeneity in these patients. In conclusion, as a first step toward understanding potential links between lung mechanics and ventilation defects, impedance predictions were made using a computational airway tree model with simulated constriction of airways related to ventilation defects measured in mild‐moderate asthmatics.